Demonstração experimental de um novo mecanismo biofísico envolvido no desenvolvimento da polipose nasal - Pezato, Rogerio [UNIFESP] (2016)
We evaluate biological factors that could influence the remodeling process in the mucosa of nasal polyposis and the biophysical consequences of this abnormal remodeling process. Initially, we evaluate the Staphylococcus aureus invasion limits in the nasal mucosa, we did not demonstrate the bone as possible reservoir for this bacterium, contrary to what is described for the nasal mucosa. We also studied the impact of mesenchymal stem cells on the inflammatory environment of the nasal polyp tissue. In this study we demonstrated the ability of these cells to mitigate the inflammatory process in the nasal polyp tissue. We end the thesis studying the mechanical properties of normal nasal mucosa and nasal polyp tissue. We found that the nasal mucosa of patients with nasal polyposis has lower increase of interstitial hydrostatic pressure than normal nasal mucosa. Using the same methodology we demonstrated that there are differences in the mechanical properties of the nasal mucosa of the inferior turbinate with the middle turbinate. In conclusion, we suggest that the imbalance between the oncotic pressure and hydrostatic pressure contributes to the formation of edema in nasal polyposis.